Effects of Carvedilol on Cardiovascular Events and Mortality in Hemodialysis Patients, A Systematic Review and Meta-Analysis (Iranian Journal of Kidney Diseases, 2020)
Carvedilol, the third generation of vasodilators; serves as the blocker of non-selective beta-adrenergic receptor and alpha1 adrenergic receptor. It could protect the cardiovascular system of patients receiving dialysis treatment. However, current clinical trials discussing the therapeutic benefit of carvedilol on patients receiving dialysis treatment remain inconsistent. Consequently, we decided to perform a meta-analysis to evaluate the clinical efficacy of carvedilol on patients receiving dialysis treatment. A search was conducted using EMBASE, Pubmed, Cochrane Central Register of Controlled Trials, Wanfang database, Chinese National Knowledge Infrastructure (CNKI), and VIP information database up to February 2020. We research publications (include English and Chinese language) that discuss the effects of carvedilol on cardiovascular events, all-cause mortality, hospitalizations or left ventricular ejection fraction (LVEF) in dialysis population. Our analysis included 4 randomized control trials and 2 observational studies. We discussed the therapeutical effects of carvedilol on all-cause mortality, cardiovascular events, hospitalizations, and LVEF of patients receiving dialysis treatment. Totally, this analysis reported 2998 hemodialysis (HD) patients. We found a significant association between carvedilol and reduced incidence of all-cause mortality, cardiovascular events and hospitalizations in HD patients. In addition, carvedilol significantly improves LVEF (n = 241; WMD = 6.95; 95% CI, 0.54 to 13.36; I2 = 90%) in HD population. Our systematic review and meta-analysis demonstrates that carvedilol is associated with a reduced incidence of cardiovascular events, all-cause mortality and hospitalizations in patients on HD. Besides; carvedilol significantly improves LVEF in HD population. Nevertheless, high-quality and well-powered evidence is still needed, so as to further confirm the impacts of carvedilol on HD patients.